2015
DOI: 10.1007/s40124-015-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Type 1 Diabetes: Closed-Loop Therapies

Abstract: The concept of a closed-loop, automated insulin delivery system, with continuous glucose sensing and insulin delivery informed by a control algorithm without patient intervention, offers the potential to decrease the burden of diabetes management and modify the significant glycemic excursions associated with conventional therapy. Closed-loop technology represents a change in the treatment paradigm for diabetes as the transition is made from primarily self-management behaviors to automated insulin therapy, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Current systems, including those being tested and one that will be available to consumers in 2017, include several components: an insulin pump, continuous glucose monitoring (CGM), and a third device that manages data from CGM to provide automated insulin delivery through the pump through the use of an algorithm. Some systems manage glucose levels overnight, while others-including the first approved by the Food and Drug Administration (FDA) in 2016 (Gordon, 2016)-are hybrid closed loop (HCL) systems which still require meal boluses but assist in managing daytime and nighttime glucose levels (Ly and Buckingham, 2015). Trials of such systems have demonstrated success through keeping participants' glucose levels within range 70-80 percent of the time (Ly and Buckingham, 2015;Russell et al, 2014Russell et al, , 2016Thabit et al, 2015aThabit et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current systems, including those being tested and one that will be available to consumers in 2017, include several components: an insulin pump, continuous glucose monitoring (CGM), and a third device that manages data from CGM to provide automated insulin delivery through the pump through the use of an algorithm. Some systems manage glucose levels overnight, while others-including the first approved by the Food and Drug Administration (FDA) in 2016 (Gordon, 2016)-are hybrid closed loop (HCL) systems which still require meal boluses but assist in managing daytime and nighttime glucose levels (Ly and Buckingham, 2015). Trials of such systems have demonstrated success through keeping participants' glucose levels within range 70-80 percent of the time (Ly and Buckingham, 2015;Russell et al, 2014Russell et al, , 2016Thabit et al, 2015aThabit et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%
“…Some systems manage glucose levels overnight, while others-including the first approved by the Food and Drug Administration (FDA) in 2016 (Gordon, 2016)-are hybrid closed loop (HCL) systems which still require meal boluses but assist in managing daytime and nighttime glucose levels (Ly and Buckingham, 2015). Trials of such systems have demonstrated success through keeping participants' glucose levels within range 70-80 percent of the time (Ly and Buckingham, 2015;Russell et al, 2014Russell et al, , 2016Thabit et al, 2015aThabit et al, , 2015b. Given these positive results, HCL systems have potential to ease daily burdens of diabetes management, improve glycemic control, and reduce risk of long-term complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not necessarily obvious to someone with little to no knowledge about T1DM. The event Lily reports is representative of the mental load associated with living with T1DM, the need to plan ahead, anticipate the effect of food, exercise, and other factors, and keep glucose levels and insulin in balance (Ly & Buckingham, 2015; Rustad et al., 2013; Tack et al., 2018). For a wider audience, this framing needs to be added.…”
Section: Creating the Exhibitionmentioning
confidence: 99%
“…Improvements in CGM technology have also helped enable advances in closed-loop technology. 11 These systems have been shown to increase the time an individual spends in target glucose range, to reduce mean glucose level, and to decrease overnight hypoglycemia. 12-15…”
mentioning
confidence: 99%